2010
DOI: 10.1037/a0019182
|View full text |Cite
|
Sign up to set email alerts
|

Solve the problem first: Constructive solution strategies can influence the accuracy of retrospective confidence judgments.

Abstract: Two experiments tested whether differences in problem-solving strategies influence the ability of people to monitor their problem-solving effectiveness as measured by confidence judgments. On multiple choice problems, people tend to use either a constructive matching strategy, whereby they attempt to solve a problem before looking at the response options, or a response elimination strategy, whereby they work backward from response options trying to find one that fits as a solution. Constructive matching gives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
54
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 59 publications
6
54
0
Order By: Relevance
“…Overall, the items in the distractor-free version proved to be more difficult than the items in the versions employing distractors. This finding is very much in line with the position of many authors [2][3][4][5][6][7]9] who differentiate between constructive matching and response elimination and propose that response elimination constitutes a fallback strategy that is used when respondents are unable to solve the items via constructive matching. As it is impossible to employ response elimination in a distractor-free version, respondents are unable to solve the items by response elimination and fail when they are unable to solve the items via constructive matching.…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…Overall, the items in the distractor-free version proved to be more difficult than the items in the versions employing distractors. This finding is very much in line with the position of many authors [2][3][4][5][6][7]9] who differentiate between constructive matching and response elimination and propose that response elimination constitutes a fallback strategy that is used when respondents are unable to solve the items via constructive matching. As it is impossible to employ response elimination in a distractor-free version, respondents are unable to solve the items by response elimination and fail when they are unable to solve the items via constructive matching.…”
Section: Discussionsupporting
confidence: 71%
“…The results of studies analyzing verbal reports and eye-tracking data have clearly indicated behavioral differences between respondents who use different strategies [2][3][4][5][6][7]. Respondents employing constructive matching have been found to spend proportionally more time inspecting the item stem before taking into account the response options and tend to toggle less between the item stem and the response options.…”
Section: Differences In Solution Strategy Outcomesmentioning
confidence: 99%
See 3 more Smart Citations